2007
DOI: 10.1002/ijc.22636
|View full text |Cite
|
Sign up to set email alerts
|

Improved anti‐cancer effect of interferon gene transfer by sustained expression using CpG‐reduced plasmid DNA

Abstract: Plasmid DNA (pDNA) expressing mouse interferon (IFN)-b or IFN-c (pCMV-Mub and pCMV-Muc, respectively) has been shown to be effective in inhibiting the growth of colon carcinoma CT-26 cells in the liver (Kobayashi et al., Molecular Therapy 2002;6:737-44). The therapeutic effect of such IFN gene transfer could be significantly increased by the sustained expression of IFNs. In the present study, CpG-reduced pDNA encoding IFN-b or IFN-c (pGZB-Mub and pGZB-Muc, respectively) was constructed. pCMV-Mub and pCMV-Muc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…28 Furthermore, the reduction in the number of CpG motifs was linked with the prolonged transgene expression from the vectors delivered by hydrodynamic injection, suggesting that CpG-depleted plasmid vectors are useful for sustained transgene expression. 11,12 Even though this conclusion seems to be valid in terms of safety or reduced cytokine production, especially when lipoplex is used for transfection, 29 our previous study rejected the hypothesis that pro-inflammatory cytokines inhibit transgene expression from plasmid vectors. 12 In our previous study, 10 the lipoplex-induced pro-inflammatory cytokines, such as tumor necrosis factor-a, IFN-g and interleukin-12, did not reduce transgene expression from plasmid vectors.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…28 Furthermore, the reduction in the number of CpG motifs was linked with the prolonged transgene expression from the vectors delivered by hydrodynamic injection, suggesting that CpG-depleted plasmid vectors are useful for sustained transgene expression. 11,12 Even though this conclusion seems to be valid in terms of safety or reduced cytokine production, especially when lipoplex is used for transfection, 29 our previous study rejected the hypothesis that pro-inflammatory cytokines inhibit transgene expression from plasmid vectors. 12 In our previous study, 10 the lipoplex-induced pro-inflammatory cytokines, such as tumor necrosis factor-a, IFN-g and interleukin-12, did not reduce transgene expression from plasmid vectors.…”
Section: Discussionmentioning
confidence: 94%
“…[8][9][10] To achieve long-term expression of IFN-g, we developed plasmid vectors that express murine IFN-g (Mug) for a long period of time. 11,12 A single administration of the newly constructed IFN-gexpressing plasmids by the hydrodynamic injection method, which is a most efficient method for in vivo gene transfer, 13 was effective in obtaining therapeutic levels of IFN-g over 480 days and in exerting marked therapeutic effects in various diseases models, including metastatic tumor and atopic dermatitis. 11,12,14 In these studies, transient expression of IFN-g showed little therapeutic effect, emphasizing the importance of sustained expression.…”
Section: Introductionmentioning
confidence: 99%
“…36 Targeting PC by molecular abnormality remains elusive because of the accumulation of multiple genetic changes during its multistep carcinogenesis. During the last decade, numerous studies illustrated the gene transfer or systemic delivery of IFN-b to inhibit tumor growth in multiple animal models from gliomas, 37 to hepatocellular carcinoma, 38 metastatic breast cancer, 39 prostate cancer, [40][41][42] rectum, colon and endometrial tumors, [43][44][45] lung tumors, 46,47 renal cell carcinomas and melanoma, 48,49 neuroblastoma, 50,51 disseminated peritoneal cancer, 52 bladder cancer, 53 malignant mesothelia 54 and fibrosarcomas. 55 Recently, a cancer gene therapy trial for gliomas based on the intratumoral administration of IFN-b) was shown to be feasible and associated with apoptosis induction.…”
Section: Lentiviral Vectors For Pc Therapy E Ravet Et Almentioning
confidence: 99%
“…In addition to these challenges, gene delivery is an option to increase the in vivo half-life of therapeutic proteins, including IFNs. In previous studies, we proved that the depletion of CpG motifs in plasmid vectors is an effective approach for extending the duration of transgene expression (20,21). We also succeeded in developing a murine IFN-g-expressing plasmid DNA, pCpGMug, which contains no CpG motifs except for those in the cDNA region (22).…”
mentioning
confidence: 99%
“…In this study, we injected pCpG-Mug, a murine IFN-g-expressing plasmid DNA, into a human atopic dermatitis model (NC/Nga mice) (23), to achieve a sustained transgene expression of IFN-g. A conventional CpG replete plasmid vector expressing IFN-g, pCMVMug (21,24), was also used for comparison to examine the importance of the duration of transgene expression on the immunological changes induced by IFN-g gene transfer. The expression profile of IFN-g was first examined in NC/Nga mice, and the effect of the expression on the level of IL-4, -5, -10, -12, -13, -17, and thymus and activation-regulated chemokine (TARC) was evaluated.…”
mentioning
confidence: 99%